Telefonoaudiologia na fissura labiopalatina: integração de serviço de alta complexidade e clínica-escola - Sausanavicius, Mariana Cristina de Azevedo [UNESP]; Cardoso, Vanessa Moraes [UNESP]; Manicardi, Flora Taube [UNESP]; Dutka, Jeniffer Rillo; Marino, Viviane Cristina de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The integration between highly complex and community health care is of fundamental importance in the management of speech, language and hearing disorders particularly for the population with cleft lip and palate. The objective of this project was to promote the integration between a craniofacial center and university clinic while providing health care services for management of communication disorders of a population with craniofacial anomalies. The program involved providing information and counseling using oral presentations and video material to guide patients and their families about cleft lip and palate and its effects on language and speech production, along with there commendation for following-up and adhering to the speech therapy schedule. Telecare was also used during students’ management of speech and language disorders at the university clinic (UNESP) as proposed within a program involving teleconsultations using virtual private network or Skype to integrate the university clinic with the craniofacial center. The project also offered opportunities for preparing students for teleducation initiatives involving access to 14 sites available on the web with information about speech disorders related to craniofacial anomalies. A total of 57subjects participated in this project including patients, families, and health and education professionals. Overall, it was observed that the telepractices in Speech-Language Pathology fostered the integration between a craniofacial center and a university clinic optimizing the diagnosis and treatment of speech disorders presented by the population with cleft lip and palate.

A integração dos serviços de alta complexidade e de atenção básica à saúde é de fundamental importância no gerenciamento das alterações de fala, de linguagem e de audição particularmente apresentadas pela população com fissura labiopalatina. O objetivo geral do projeto é promover a integração entre um serviço de alta complexidade e uma clínica-escola do Curso de Fonoaudiologia, proporcionando cuidados de saúde para o gerenciamento dos distúrbios da comunicação de uma população com anomalias craniofaciais. O programa envolveu o fornecimento de informações e aconselhamento por meio de exposições orais e/ou vídeos educativos para orientar os pacientes e suas famílias sobre fissura labiopalatina e seus efeitos na linguagem e na produção da fala, juntamente com a recomendação para acompanhar e aderir a terapia fonoaudiológica. A Teleassistência também foi utilizada durante o gerenciamento das alterações de fala e da linguagem pela clínica-escola (UNESP), conforme proposto dentro de um programa envolvendo teleconsultas usando a rede virtual ou Skype para integrar a clínica universitária com o centro craniofacial. O projeto também ofereceu oportunidades para preparar os alunos para as iniciativas de Teleducação que envolveram o acesso a 14 sites disponíveis na web com informações sobre alterações de fala relacionadas com anomalias craniofaciais. Um total de 57 indivíduos participaram neste projeto, incluindo pacientes, famílias e profissionais de saúde e educação. No geral, observou-se que a telefonoaudiologia promoveu a integração entre serviço de alta complexidade e uma clínica-escola, além de otimizar o diagnóstico e o tratamento de distúrbios da fala apresentadas pela população com fissura labiopalatina.
Keywords: Speech-language pathology; Cleft lip and palate; Telecare; Fonoaudiologia; Fissura labiopalatina; Teleassistência